Evil and the Mystics’ God - Stoeber, Michael. author. aut Link
IX, 225 p.
Keywords: Certain mystics provocatively respond to the challenges which evil poses to their religious beliefs. This book develops the structure of the mystical response to evil together, drawing upon the work of Eckhart, Boehme, Dostoevsky, Sankara, Ghose and Underhill.